Religious Tourism Destinations : Segara Kenjeran Temple and Jagat Karana Temple, Surabaya - A.A. Merthawati (Bali Tourism Board, 2024)
This article aims to describe the religious tourism destinations in Surabaya, East Java. The objects of study are Jagat Karana Temple and Segara Kenjeran Temple. The objects were chosen because those temples are two significant temples located in the capital of Surabaya. This study employs a descriptive qualitative approach. The analysis framework is based on the Guidelines for Developing Historical and Cultural Heritage Tourism (2019), which comprises four components: cultural products, narrative products, tourism products, and destination products. Data were collected through observations and a literature review on tourism, cultural tourism, religious tourism, and the profiles of Jagat Karana Temple and Segara Kenjeran Temple. Finding shows as tourism destinations, both temples offer unique attractions that support the development of cultural tourism. Jagat Karana Temple’s central location in Surabaya, along with amenities such as bale gong and wantilan, as well as its easy accessibility, makes it a prominent religious tourism destination. Similarly, Segara Kenjeran Temple, located in the popular Kenjeran Beach area with amenities such as gazebos and gardens, provides a serene and accessible destination. Both temples are integral to religious and cultural tourism routes, offering experiences that combine spirituality, architecture, and natural beauty, making them worthy destinations for visitors.